FAKTOR PENENTU KEBERHASILAN PROGRAM KREDIT USAHA RAKYAT TERHADAP PENINGKATAN AKSES PERMODALAN DI PROPINSI JAWA TIMUR - Ike Kusdyah Rachmawati (University of Merdeka Malang, 2012)
This study aimed to analyze the critical success factors program peoples business credit against increasingcapital access in East Java. It used qualitative and quantitative approaches and it used descriptive analysis thatanalyzed the contribution program assistance to micro and small groups and various internal and externalconstraints, and used Analytic Hierarchy Process (AHP) to determine the priority level of the factors thataffected the Kredit Usaha Rakyat (KUR). Sample of this study was the banking, micro business, small business,business and service / technical institutions in East Java. The research was done in the 3 (three) districts whichwere Sidoarjo regency, Malang and Surabaya. Based on the results of the AHP, access to services and KURperformance could be improved by considering some factors and sub factors that influenced it, among others:candidates prospects debtor, office of technical capacity, policy and resources banking, and macro factors.Macro factors were factors that should always be monitored. The responsible party for this macro was a BIfactor as the banking authorities.